La représentation nomographyque d’une classe de systèmes d’équations par des nomogrammes a transparent orienté avec des familles des lignes côtées: The nomographic representation of a class of equation systems using oriented transparent nomograms with families of scaled lines. - Ionescu, Gh. D.; Boşilcă, Poliana; Dumitraş, Daria (Anal. Numér. Théor. Approx., 1980)
Not available.